Rainfall Thresholds for Landslide Prediction in Loano Subdistrict, Purworejo District Central Java Province - Farma Dyva Ferardi; Wahyu Wilopo; Teuku Faisal Fathani (Geological Engineering Department Universitas Gadjah Mada, 2018)
Purworejo Districtis a district with high disaster risk index in Indonesia, especiallylandslide. The main factor that triggers the landslide is rainfall. However, therehas been no comprehensive research on the intensity of rain that triggered the landslide in Purworejo District, especially in the Sub district of Loano. Huge landslide occurred in Loano Sub district at 2016, causing 46 deaths and damages in several houses. Therefore, it is necessary to study the prediction of landslide based on rainfall data and geological conditions of Loano Sub district, Purworejo District. The objective of this research is to analyze the mechanism of landslide, to analyze the rainfall that triggers the landslide and to estimate the intensity of rain that can triggers the landslide. The research method is collecting historical data of landslides in Purworejo District along with rainfall data, geological observation that includes the condition of lithology, geomorphology and hydrogeology,undisturbed soil sampling in Loano Sub district. The prediction of landslide uses empirical methods which were then simulated by Geostudio 2012 Software. The results show that the type of landslide is sliding, the main control factor is the steep slope and the thickness of the soil. The rainfall threshold triggering landslide are as follows for lithology andesite breccia I = 81.782 D????1.197, sandy clay I = 92.579 D????0.13, and andesite intrusionI = 145.32 D????0.338.